Decision Support for Difficulties in a Furniture Manufacturing Company - Bakon, Krisztián (International Journal of Engineering and Management Sciences, 2020)
In “Decision support for difficulties in a furniture manufacturing company” titled work we are presenting in detail the operation of a particular furniture company and the difficulties encountered during its operation, which they try to overcome in some way so that they do not hinder the operation of the company. After that, we will show how we wanted to achieve the production support system. In different versions, we detail what we actually wanted to accomplish while showing results that illustrate the evolution of the system. We also present the difficulties of the development, which is made in Java. We also present the latest version of the system and its results. After processing the input parameters, the system is able to produce results using scheduling algorithms that can help in making important decisions during production planning.